APPLYING SMART(SELF-MONITORING APPROACHTO READING AND THINKING) STRATEGY FOR ENHANCING STUDENTS’ SKILL IN READING COMPREHENSION - Rachmanita (Universitas Islam Ogan Komering Ilir Kayuagung, 2019)
Reading is essential either for students’ careers or for study purposes. In the same time, it is a complex skill that involves all of higher mind in order to understand what is read. Many students find it hard to read. Among the reading problem exhibited by students at secondary school is the inability to bring out fact from the passage, poor retention and recall of what is read, and a weak vocabulary base. Therefore, the aim of this study was to find out whether or not there wasasignificant difference in reading achievement between the students who were taught by using Self-Monitoring Approach to Reading and Thinking (SMART) Strategy and that of those who were not. Quasi-experimental method and nonrandomized pre-test post-test control group were used. The sample was chosen by using purposive sampling method. Content validity was used to check the validity and try out was applied to find out the reliability of the test. Reading comprehension test in the form of multiple-choice was usedin collecting the data. In analyzing the data, t-test was used. Then SPSSProgram version 16was used to calculate the data. The result showed that the mean difference between posttest in the experimental and control group was 21.90, tobtainedwas 11.08, and the critical value of ttablewas 1.99. Since tobtained (11.08) was higher than ttable (1.99) and pvalue (0.00) was less than άvalue (0.05). It meant that there was a significant difference in students’ reading achievement between the students who were taught using Self-Monitoring Approach to Reading and Thinking (SMART) strategy and that of those who were not